STATE RESPONSIBILITY OVER SAFETY AND SECURITY ON AIR NAVIGATION OF CIVIL AVIATION IN INTERNATIONAL LAW - Simatupang, Andika Immanuel (Indonesian Journal of International Law, 2016)
The Uberlingen Mid-Air Collision which happened in Germany in 2002 between Bashkirian Airlines and DHL had attracted the international community to international civil aviation activities. Bashkirian then brought this case before the Dictrict Court in Konstanz which sued Republic of Germany to indemnify the company for damage claims against the airine by third parties. The Court then decided Germany should responsible to Bashkirian and indemnify all the cost claimed against the airline. The collision occured at German’s territory which controlled by Skyguide. This thesis is aimed to elaborate the state liability on safety and security of air navigation in its territory which failure to do so will result a state responsibility. This thesis will analyze the provisions and the state’s liabilities in providing the safe air navigation facilities according to international law